KEPUTUSAN PEMBELIAN SEPEDA MOTOR BEKAS DI KALANGAN MAHASISWA UNIVERSITAS TEKNOLOGI SUMBAWA - Muhammad Nur Fietroh; S Suhaedi (Pusat Riset dan Publikasi, 2021)
This study was to examine the effect of product quality, price and brand image on the decision to purchase a used motorcycle. This research is a research with quantitative method through associative sampling approach as many as 100 respondents taken using non-probability sampling with incidental sampling method. The data collection method used a questionnaire. The results showed that the variables of product quality, price and brand image had a positive and significant effect on purchasing decisions.